Transesterification of edible and nonedible vegetable oils with alcohols over heteropolyacids supported on acid-treated clay - Bokade, Vijay V.; Yadav, Ganapati D. (Industrial & Engineering Chemistry Research, 2009)
In the current work, the novelty of heteropolyacid on clay (K-10) for the transesterification of vegetable oil with lower and higher alcohols is presented. Methyl esters (biodiesel) and glycerol were produced by the transesterification of vegetable oil with methanol in the presence of dodecatungestophosphoric acid (DTPA) supported on K-10 clay. The transesterification consists of three consecutive reversible reactions Diglycerides (DG) and monoglycerides (MG) are intermediate products. The optimal catalyst concentration was 5% w/w of oil. Detailed studies were done for optimization of the process parameters. The rate of transesterification in a batch reactor increased with temperature up to 170 degrees C. Higher temperatures did not reduce the time to reach maximum conversion. The study was also extended to reactions of different edible and nonedible oils with lower and higher alcohols. The conversion of TG, DG, and MG seemed to be a second-order mechanism for the forward and reverse reactions, where the reaction system could be described as a pseudo-heterogeneous catalyzed reaction. The reaction rate constants for the TG. DG, and MG transesterification reactions were 0.12-0.84 h(-1) and were higher for the MG reaction than for the TG transesterification. The activation energies were 4.2, 26, and 7.4 kcal/mol for the TG, DG, and MG transesterification reactions, respectively. The proposed kinetic model fits the experimental results well.